If it's not what You are looking for type in the equation solver your own equation and let us solve it.
107=-7m+6(-3m-3)
We move all terms to the left:
107-(-7m+6(-3m-3))=0
We calculate terms in parentheses: -(-7m+6(-3m-3)), so:We get rid of parentheses
-7m+6(-3m-3)
We multiply parentheses
-7m-18m-18
We add all the numbers together, and all the variables
-25m-18
Back to the equation:
-(-25m-18)
25m+18+107=0
We add all the numbers together, and all the variables
25m+125=0
We move all terms containing m to the left, all other terms to the right
25m=-125
m=-125/25
m=-5
| j-j+j+4j+4j=9 | | 0.9(w+-20)=-7.2 | | 5=-7a+8+4 | | t-11=13 | | 6t=96 | | 4n-2=44 | | 14-8m=-13-5m | | |3x+5|+10=7 | | -5-9x=3-(2-3x)-8 | | 2y+0.9=-1.04 | | 8(2x-5)-4x=-10+7x | | 4(b-65)=76 | | -342=-9x | | -x+3=4x-17/ | | 4x-8=10x-2 | | −4x+3=23. | | 1=3n | | 2(m-4)=8+2m | | a-1.7=-4.9 | | 23x-3=17 | | 2p-10=32 | | 4(4x-7)-5=16x-33 | | X^2+6x-7=x+3+5 | | 4=g/10 | | 2/3t-5=2 | | 33-(2c+3=2(c+5)+c | | t+22=6 | | -3z+-7=2 | | b/3-8=-4.5 | | -b+2(-3b+8)=23-6b | | r+-6=1 | | 5=1/4x+2 |